Bio‐inspired Synthesis of Energetic Microcapsules Core‐Shell Structured with Improved Thermal Stability and Reduced Sensitivity via In Situ Polymerization for Application Potential in Propellants. Issue 23 (10th November 2021) - Chen, Ling; Li, Qiang; Liu, Shishuo; Bei, Yiying; Ding, Yajun; Liu, Jie; He, Weidong
Abstract: To further improve the comprehensive performances of conventional nitramine energetic crystals hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX), 1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocane (HMX), and 2, 4, 6, 8, 10, 12‐hexanitro‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane (CL‐20), especially their thermal stability and safety properties, is the main pursue in the field of energetic materials. Enlightened by means of the composition of attachment proteins from mussels, this research demonstrates that polydopamine (PDA) self‐polymerization could be used to prepare core‐shell structure energetic composites by surface coating technology. The results reveal that energetic crystal cores are mostly well‐coated by PDA more than 6 h; the combined characteristics of explosives and PDA indicating the main interface interaction force is hydrogen bonding. Moreover, the optimal polymorph of HMX (β) and CL‐20(ε) are maintained in the preparation process. Besides, another interesting phenomenon can be observed that the polycrystalline phase transition of endothermic and the decomposition temperature of exothermic peak for energetic crystals have been increased evidently, benefitting from the heat resisting of PDA layer. Moreover, thermal decomposition has been studied and calculated under different heating rates. Furthermore, the impact sensitivity of the PDA modified composites obtained is tested as well and decreased by 2–4 times compared with pristine energetic crystals. Therefore, this fabrication strategy in this study would provide a potential application of energetic@PDA in high‐strength and high‐energy propellants. Abstract : The obtained core‐shell structure energetic composites in scanning electron microscopy images exhibit a uniform distribution in Raman mapping, and present a remarkable improved thermal stability performance.